Survival Analysis of Surgically Resected ypN2 Lung Cancer after Neoadjuvant Therapy - İşgörücü, Özgür; Citak, Necati (The Thoracic and Cardiovascular Surgeon, 2022)
Introduction Surgery is widely accepted today when downstaging of mediastinal lymph nodes after neoadjuvant therapy is achieved. However, the role of surgery in patients with persistent N2 disease is still controversial. This study aims to detail the diagnostic problems, prognostic features, and long-term survival of the persistent N2 non-small cell lung cancer patient group.Patients and Methods One-hundred fifty patients who received neoadjuvant therapy and subsequently underwent resection, in-between 2003 and 2015, were retrospectively analyzed. In this study, “persistent N2” group refers to patients who received neoadjuvant therapy for clinically or histologically proven N2, who underwent a surgery after having been classified as “downstaged” at restaging, but in whom ypN2 lesions were subsequently confirmed on the operative specimens. Patients with multistation N2 were included in the study. There were 119 patients who met the criteria, whereas persistent ypN2 was detected in 28.5% (n = 34) of all patients.Results Overall 5-year survival rate was 47.2%, while it was 23.4% for patients with persistent N2. Factors that adversely affected survival were to have nonsquamous cell histological type (p = 0.006), high ypT stage (p = 0.001), persistent N2 (p = 0.02), and recurrence during follow-up (p < 0.001). A trend toward a shorter survival was observed when the ypN2 zone was subcarinal versus other zones, but did not reach statistical significance (p = 0.08). In addition, a trend toward a shorter survival of patients with multiple N2 involvement (p = 0.412) was observed.Conclusion In the persistent N2 group, when multiple involvement or subcarinal involvement was excluded, relatively good survival was detected.
Keywords: surgery; chemotherapy; lung cancer; diagnosis